Charles Babbage (1791 + 200 = 1991) - Stigler, George J. (Journal of Economic Literature, 1991)
CHARLES BABBAGE deserves full membership in the club of mathematicians who have made significant contributions to economics, a club which began with Daniel Bernoulli (1738) and reaches at least to John von Neumann (1944). It is appropriate that Babbage's contributions were wholly nonmathematical, for his talents were richly varied and his behavior wonderfully eccentric. The invention of those ancestors of the modern computer, the Difference Machine and the Analytical Machine, is of course his greatest claim to fame: they are prodigies of both theoretical creativity and mechanical implementation. The Difference Machine was designed to produce and print mathematical tables by the use of finite differences. By 1822 Babbage had a small working model and was promising soon to produce logarithmic tables as cheap as potatoes. In building a large machine-which continually grew in power and complexity-he encountered and overcame innumerable analytical and mechanical problems. The work on the machine ground to a halt about 1832, after the Treasury refused to add to its previous grants of E12,000. Soon Babbage turned to the Analytical Machine, which consisted of two parts: